2022
DOI: 10.1177/15353702211069986
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and retinal diseases in preclinical and clinical studies: Insights and review of literature

Abstract: Metformin is one of the most prescribed drugs in the world giving potential health benefits beyond that of type 2 diabetes (T2DM). Emerging evidence suggests that it may have protective effects for retinal/posterior segment diseases including diabetic retinopathy (DR), age-related macular degeneration (AMD), inherited retinal degeneration such as retinitis pigmentosa (RP), primary open angle glaucoma (POAG), retinal vein occlusion (RVO), and uveitis. Metformin exerts potent anti-inflammatory, antiangiogenic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…Fourth, the findings provide good rationale and references for the conduction of clinical trials to verify the beneficial effects of metformin on AMD. A phase 2 clinical trial is being conducted to investigate metformin’s effect on AMD [ 57 , 58 ] and a recent study suggested that the effect of anti-VEGF in the treatment of diabetic macular edema could be enhanced by metformin [ 59 ]. Some bio-nanotechnologies are being developed to improve the delivery of metformin and probucol as potential antioxidants to block the formation of reactive oxygen species for the treatment of chemotherapy-induced hearing loss [ 60 ] or age-related hearing loss [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the findings provide good rationale and references for the conduction of clinical trials to verify the beneficial effects of metformin on AMD. A phase 2 clinical trial is being conducted to investigate metformin’s effect on AMD [ 57 , 58 ] and a recent study suggested that the effect of anti-VEGF in the treatment of diabetic macular edema could be enhanced by metformin [ 59 ]. Some bio-nanotechnologies are being developed to improve the delivery of metformin and probucol as potential antioxidants to block the formation of reactive oxygen species for the treatment of chemotherapy-induced hearing loss [ 60 ] or age-related hearing loss [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin has been shown on a cellular level to regulate lipid metabolism, inhibit vascular endothelial growth factor and inflammation, mediate oxidative stress, and prevent retinal cell death. [4][5][6]20 Additionally, in a recent study by our group, we queried a large bioinformatics database of genes associated with AMD, wet AMD, dry AMD, intermediate AMD, and geographic atrophy to identify potential drug candidates that may have interactions with AMD-related genes. This study found that of the 77,146 drugs queried, metformin was the 1st potential drug candidate for wet AMD-related genes, 13th for dry AMD-related genes, and 21st for all AMD-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…21 Therefore, it may have promise as a drug candidate for the prevention of AMD and nAMD, especially as it is an food and drug administration (FDA)-approved treatment for Type 2 diabetes and has few side effects. 20 In addition, it has been used safely without causing hypoglycemia and offers a similarly favorable safety profile in the treatment of other conditions, including polycystic ovarian syndrome, prediabetes, and obesity, and is being studied in others, including cardiovascular disease, malignancy, and age-related dementia. 22 Although a positive association between diabetes and AMD is documented in the literature, [23][24][25] the association between DR and AMD has been inconsistently demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary effects of metformin have been attributed to the activation of the metabolic regulator AMP-activated protein kinase and the potent antioxidant enzyme peroxiredoxin-2 [ 454 ]. Metformin has been proposed as a treatment for ocular conditions associated with mitochondrial dysfunction [ 455 , 456 , 457 ]. Retrospective studies have shown a modest trend of a reduced risk of AMD in subjects taking metformin, though confounding factors such as the presence of cardiovascular disease and diabetes have likely contributed to conflicting findings [ 458 ].…”
Section: Targeting Oxidative Stress In Agingmentioning
confidence: 99%